Endoscopic evaluation of dyspeptic patients (Bangladesh Medical Journal, 2014)
It was observed that most of the dyspeptic patients are showing normal endoscopic findings. In this study our aims were to obtain the endoscopic findings in patient having dyspeptic symptoms and to improve the management of patient in the light of the findings that are more common. This cross sectional descriptive hospital based study was carried out in the gastroenterology department of the Shaheed Suhrawardy Medical College Hospital, Dhaka. A total 72 cases were included in this study based on the selection criteria. Among them 46 were male and 26 were female patients. Most of the dyspeptic patients had normal endoscopic findings (55.6%). Gastric erosion was found in 22.2%, reflux oesophagitis in 8.3% cases and rest were duodenal ulcer, duodenal erosions and gastric ulcer. DOI: http://dx.doi.org/10.3329/bmj.v42i3.19001 Bangladesh Med J. 2013 Sept; 42 (3): 82-84